Role of Connexin 43 phosphorylation on Serine-368 by PKC in cardiac function and disease - Pun, Renju; Kim, Michael H.; North, Brian J. (Frontiers in Cardiovascular Medicine, 2023)
Intercellular communication mediated by gap junction channels and hemichannels composed of Connexin 43 (Cx43) is vital for the propagation of electrical impulses through cardiomyocytes. The carboxyl terminal tail of Cx43 undergoes various post-translational modifications including phosphorylation of its Serine-368 (S368) residue. Protein Kinase C isozymes directly phosphorylate S368 to alter Cx43 function and stability through inducing conformational changes affecting channel permeability or promoting internalization and degradation to reduce intercellular communication between cardiomyocytes. Recent studies have implicated this PKC/Cx43-pS368 circuit in several cardiac-associated diseases. In this review, we describe the molecular and cellular basis of PKC-mediated Cx43 phosphorylation and discuss the implications of Cx43 S368 phosphorylation in the context of various cardiac diseases, such as cardiomyopathy, as well as the therapeutic potential of targeting this pathway.